Research progress and prospect of aero-engine maintenance technology - HOU Tinghong; ZHOU Ping; HE Liming; HAN Changfu (Hangkong gongcheng jinzhan, 2023)
Aero-engine is a device that provides power for aviation equipment. Maintenance is an important stage in ensuring that the engine completes its service cycle. With the continuous development of the aero-engine maintenance industry, aero-engine maintenance technology is also constantly improved to meet the future demand for large-scale, high-quality, and efficient maintenance. The development history of aero-engine maintenance is introduced briefly. This article summarizes the research progress of aero-engine maintenance technology from three aspects: fault inspection, machine cleaning, and machine assembly. It elaborates on the progress of aircraft engine remanufacturing from three aspects: remanufacturing development, key technologies, and technological development processes; and the future development of aero-engine maintenance and remanufacturing technology was prospected.